Comunicación intercultural: Aportes de la pragmática y de la teoría proxémica en el estudio de las relaciones interculturales (2005)
In this article, we talk about intercultural communication from a pragmatic point of view. We will present, in detail, interaction notions, context, culture, and the proxemic theory. These factors will serve as a reflection around testimonies provided by an intercultural communication seminar held at the campus of Lovaina the New, in Belgium. Finally, we will present some notions of cultural shock, negotiation, and meta-communication, as key concepts to face conflicting intercultural relations and for achieving a satisfactory cultural integration.